Understanding leptin’s influence on calf development: A review of metabolic and reproductive mechanisms - Tóth, Eszter; Rátky, József; Posta, János; Knop, Renáta (Acta Agraria Debreceniensis, 2025)
Leptin, a hormone primarily produced by adipose tissue, regulates the energy balance, metabolism, and reproductive functions. This review explores leptin’s role in calf development from embryogenesis to puberty. Leptin expression is strongly influenced by the nutritional status, with circulating levels dependent on adipose tissue mass and modulated by metabolic hormones such as insulin and glucocorticoids. It plays a regulatory role in the embryonic cell division, adipogenesis, and postnatal energy metabolism. Additionally, leptin modulates appetite, the growth hormone secretion, and the reproductive system maturation. Its presence in the colostrum and milk highlights its significance in the early calf development, influencing the neonatal metabolism and immune function. As calves approach puberty, leptin serves as a key metabolic signal for reproductive maturation. A deeper understanding of leptin’s multifunctional role in calf development could contribute to improved livestock growth and reproductive management strategies.